Scenario-based seismic risk assessment in the city of Aigion (Greece) - Giannaraki, G.; D. Kazantzidou-Firtinidou; Kassaras, I.; Roumelioti, Z.; A. Ganas; C. Karakostas; S. Mourloukos; P. Stoumpos; C. Tsimi (16th European Conf. on Earthq. Eng. (16ECEE), 2018)
A seismic risk model on a building block scale is presented for the earthquake prone city of Aigion (W. Corinth Gulf) by combining deterministic seismic hazard with Risk-UE LM1 structural vulnerability, assessed per building, taking into account site conditions approximated by Horizontal-to-Vertical-Spectral-Ratios (HVSR) from ambient noise. The stochastic finite-fault method has been applied to simulate strong ground motion from two close earthquake scenarios, capable of occurring within the seismotectonic frame of the area: (a) a repetition of the 1995, June 15 (Mw=6.4) devastating earthquake and (b) a repetition of the 1861, December 26 earthquake of Mw=6.7 on the East Heliki Fault (EHF). The applied methodology provided comparable pattern with the real damage distribution of the 1995 earthquake, highlighting outlooks toward earthquake preparedness and risk mitigation purposes.